Upaya Peningkatan Status Gizi Anak Melalui Program Posyandu Balita "Anggrek Merah" Kelurahan Karang Anyar Pantai - Nurul Hidayat; Gea Dilah Hermila; Jesika Dela Maharani; Fahrul Ilham Muhti; Owen Petit; Prithi Arvana Angody; Febrianingsih. A; Nanda Saputra (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Nutritional problems in toddlers remain a public health challenge in Indonesia, including in Tarakan City, North Kalimantan. The 2018 Basic Health Research (Riskesdas) data shows a high prevalence of malnutrition, severe malnutrition, and stunting in toddlers, with data showing that based on the body weight index (BB/A) the prevalence of malnourished toddlers is 3.9% while 13.8% of toddlers are undernourished. Based on the height-for-age (H/A) index, there are 11.5% of toddlers with very short nutritional status and 19.3% of toddlers with stunted nutritional status. Meanwhile, based on the weight-for-height (BB/H) index, the proportion of very wasted children is 3.5%, undernourished children are 6.7%, and overweight children are 8% (Riskesdas, 2018). Because of these problems, early nutrition education efforts are needed. This community service activity aims to increase the knowledge of toddler mothers about the importance of balanced nutrition for children, especially through the use of UHT milk as a nutritional supplement, as well as strengthening the role of integrated health posts (Posyandu) in monitoring child growth and development. Thus, this community service activity contributes to raising public awareness of the importance of meeting toddler nutritional needs and is expected to support government programs to reduce the prevalence of stunting in Tarakan City.